ISLAM AS COMMON CULTURAL HERITAGE IN POST-STALINIST DAGHESTAN: FROM IJTIHAD TO ENLIGHTENMENT - Kemper, Mihael' (History, Archeology and Ethnography of the Caucasus, 2018)
From the beginning of the 1960s, actors of different Daghestani nationalities initiated a re-evaluation of the role of Islam in the history of Daghestan. An important historical personality to draw upon was Muhammad al-Quduqi, a Daghestani Islamic legal scholar of the late seventeenth and early eighteenth centuries. Quduqi was known for his sympathies towards ijtihad (Islamic legal reasoning by analogy) and for his call to replace customary law by Islamic law. This article studies how Quduqi was brought back into Soviet discourse in 1960, and how his advocacy for ijtihad was subsequently interpreted in Marxist terms as a quest for philosophy, rationalism and progress, with secularizing terms drawn from the discourse of Daghestani Jadids of the 1920s and 1930s. A comparison is then made with Soviet Tatarstan, where Soviet Marxist historians constructed a similar autochthonous trajectory of Tatar-Islamic progress and enlightenment. In both cases, Islamic concepts were taken out of context and used for the construction of a secularized national Muslim cultural heritage (miras) that would prepare the ground for socialism - with the difference that in Daghestan, this Muslim Mirasism was multi-ethnic in character.
Keywords: Daghestan; Islamic Law; Soviet Union; Mirasism; Tatarstan